The association of hypertensive disorders of pregnancy with small for gestational age and intertwin birthweight discordance. Issue 7 (20th May 2021) - Lin, Dongxin; Luo BD, Caihong; Chen, Gengdong; Fan, Dazhi; Huang, Zheng; Li, Pengsheng; Wu, Shuzhen; Ye BD, Shaoxin; Ma, Huiting; Rao, Jiaming; Zhang, Huishan; Chen, Ting; et al.
Abstract: Available evidence shows conflicting results regarding the association between hypertensive disorders of pregnancy (HDPs)/preeclampsia (PE) and small for gestational age (SGA) and birthweight discordance (BWD). This retrospective study of 2131 twin pregnancies aimed to evaluate the association of HDPs/PE with the presence of SGA and BWD. The eligible pregnancies were categorized into four study groups: concordant pairs without SGA fetuses, discordant pairs without SGA fetuses, concordant pairs with SGA fetuses, and discordant pairs with SGA fetuses. We applied binary logistic regression models to compare the incidence of HDPs/PE and multinomial logit regression models to evaluate the severity of PE between the study groups. The models were adjusted for potential confounders. Increases in HDPs were observed in concordant (aOR, 2.33; 95% CI: 1.46–3.73) and discordant (aOR, 3.50; 95% CI: 2.26–5.43) pregnancies with SGA fetuses but not in discordant pregnancies without SGA fetuses (aOR, 1.42; 95% CI: 0.81–2.49); increases in PE were also found in concordant (aOR, 1.87; 95% CI: 1.08–3.23) and discordant (aOR, 3.75; 95% CI: 2.36–5.96) pregnancies with SGA fetuses but not in discordant pregnancies without SGA fetuses (aOR, 1.34; 95% CI: 0.71–2.52). Discordant pregnancies with SGA fetuses were associated with severe PE (aRRR, 3.48; 95% CI: 1.79–6.77), whereas concordant pregnancies with SGA fetuses were associated with only mild PE (aRRR, 2.54; 95% CI: 1.33–4.88). Our results suggest that SGA is associated with the development of HDP/PE, while discordant growth is associated with the severity of PE. These associations need to be further investigated using estimated fetal weight (EFW).